Taurine enhances spermatogenic function and antioxidant defense mechanisms in testes and epididymis of L-NAME-induced hypertensive rats (2018)
The beneficial health effects of taurine on hypertension have been demonstrated previously in both experimental and epidemiological studies. However, the role of taurine in reproductive dysfunction associated with hypertension has not been investigated. The present study evaluated the therapeutic efficacy of taurine on reproductive deficits in N-nitro-L-arginine methyl ester (L-NAME)-induced hypertensive rats. Sixty male Wistar rats were randomly assigned into six groups namely control, taurine alone, L-NAME alone (40 mg/kg) or L-NAME treated with either taurine (100 and 200 mg/kg) or reference drug atenolol (10 mg/kg) for 28 consecutive days. Results indicated that taurine treatment significantly abrogated L-NAME-induced increase in systolic, diastolic and mean arterial pressures when compared with hypertensive control. Administration of taurine markedly increased antioxidant enzymes activities and glutathione level, whereas it suppressed the increase in biomarkers of oxidative stress in the testes and epididymis of L-NAME-induced hypertensive rats. Moreover, taurine significantly reversed hypertension mediated decreases in circulatory concentrations of luteinizing hormone, follicle- stimulating hormone and testosterone whereas it increased testicular sperm number, epididymal sperm number and sperm progressive motility in the hypertensive rats. Furthermore, taurine abrogated the suppression of marker enzymes of testicular function namely acid phosphatase, alkaline phosphatase and lactate dehydrogenase and preserved the histo-architectures of the testes and epididymis in L-NAME-induced hypertensive rats. Taken together, the findings from this study highlight the beneficial role of taurine in reproductive system of L-NAME-induced male hypertensive rats. Taurine supplementation may be a good clinical approach to prevent reproductive deficits in male hypertensive patients.